PENGARUH BAURAN PEMASARAN TERHADAP KEPUASAN KONSUMEN DI GOSYEN BAKERY SURABAYA - Vingki Kurnia Sari; Mei Indrawati (Jurnal Ekonomi, Bisnis dan Social, 2023)
The purpose of this study was to analyze product quality, price, location, and promotion of consumer satisfaction at Gosyen Bakery Surabaya. Sampling method using purposive sampling. The number of samples used in this study were 100 consumer respondents at Gosyen Bakery Surabaya. The scope of this research is only on variables related to product, price, location, and promotion of consumer satisfaction. Services that directly or indirectly affect customer satisfaction. The approach of this research is the quantitative approach method. The data analysis technique of this research uses the Multiple Linear Regression analysis method with the SPSS application program.